DAMPAK PERTUMBUHAN SERTA KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN SEBELUM COVID-19 DAN MASA NEW NORMAL TERHADAP PAJAK DAERAH KABUPATEN MUSI BANYUASIN - Farida Aryani (Institut Rahmaniyah Sekayu, 2022)
This study analyzes the growth impact and contribution of hotel and restaurant taxes before Covid-19 and the new normal period on regional taxes in Muba Regency. The data used are primary and secondary. Data analysis techniques use quantitative descriptive analysis. The research results show that during Covid-19 in 2020, hotel tax growth fell 17.35% and restaurant taxes fell 26.22% compared to 2019 and during the new normal period 2021 hotel taxes increased 18.30% and restaurant taxes 36.11% compared to 2020. The contribution of hotel tax to local taxes is still very low, 2019 was 1.24%, 2020 decreased to 1.03% and 2021 increased 1.38%, so it is categorized as less contributing because the percentage is less than 1.9%. Meanwhile, the contribution of restaurant tax in 2019 was 17%, decreased 13% in 2020 and increased 20% in 2021, so it is categorized as a very large contribution because the percentage is more than 4% of the Muba regional tax. Thus, the Covid-19 has had a negative impact on the growth and contribution of hotel and restaurant tax revenues to the regional taxes of Muba Regency.